Temporal characteristics of aerosol optical properties over the glacier region of northern Pakistan. (May 2019) - Zeb, Bahadar; Alam, Khan; Sorooshian, Armin; Chishtie, Farrukh; Ahmad, Ifthikhar; Bibi, Humera
Abstract: Glacier melting due to light-absorbing aerosol has become a growing issue in recent decades. The emphasis of this study is to examine aerosol loadings over the high mountain glacier region of northern Pakistan between 2004 and 2016, with sources including local emissions and long-range transported pollution. Optical properties of aerosols were seasonally analyzed over the glacier region (35–36.5°N; 74.5–77.5°E) along with three selected sites (Gilgit, Skardu, and Diamar) based on the Ozone Monitoring Instrument (OMI). The aerosol sub-type profile was analyzed with Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO). Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model was used to understand the origin of air masses arriving in the study region. The highest values of aerosol optical depth (AOD) and single scattering albedo (SSA) occurred during spring, whereas aerosol index (AI) and absorption AOD (AAOD) exhibited maximum values in winter and summer, respectively. The minimum values of AOD, AI, AAOD, and SSA occurred in winter, autumn, winter, and autumn, respectively. The results revealed that in spring and summer the prominent aerosols were dust, whereas, in autumn and winter, anthropogenic aerosols were prominent. Trend analysis showed that AI, AOD, and AAOD increased at the rate of 0.005, 0.006, and 0.0001 yr −1, respectively, while SSA decreased at the rate of 0.0002 yr −1 . This is suggestive of the enhancement in aerosol types over the region with time that accelerates melting of ice. CALIPSO data indicate that the regional aerosol was mostly comprised of sub-types categorized as dust, polluted dust, smoke, and clean continental. The types of aerosols defined by OMI were in good agreement with CALIPSO retrievals. Analysis of the National Oceanic and Atmospheric Administration Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model revealed that air parcels arriving at the glacier region stemmed from different source sites. Graphical abstract: Image 1 Highlights: The results revealed the presence of absorbing aerosol over the glacier region. The analysis showed an increasing trend of AOD, AI & AAOD over studied region. CALIPSO showed an evidence of dust, smoke, polluted dust & clean continental aerosol. OMI retrieved aerosol types were in good agreement with CALIPSO retrievals.